§ 2.

                   17. f(x)
g(x) .

17.01.

f(x) = x4 + 2x3 17x2 12 + 20;

 

g(x) = 4 4x3+3x2+2x20;

17.02.

f(x) = 4x4 + 2x2 + 2 + 2;

 

g(x) = 34 6x3+8x25x+2;

17.03.

f(x) = 2x4 14x3 + 28x2 16;

 

g(x)=2415x3 +34x225x+4;

17.04.

f(x) = 4x4 + 4x3 17x2 + 4;

 

g(x) = 34 + 5x3 10x2 8x;

17.05.

f(x) = x4 + x3 13x2 6 + 12;

 

g(x)=45x3 + 3x2 + 10 4;

17.06.

f(x) = 2x4 15x3+14x2+40+15;

 

g(x) = 24 11x3 +2x2129;

17.07.

f(x) = 4x4 + 10x3 3x2 2 2;

 

g(x) = 24 + 2x3 5x2 +106;

17.08.

f(x) = x4 2x3 + 12;

 

g(x) = 24 5x3 8x2+15+12;

17.09.

f(x) = 4x4 +14x315x213+5;

 

g(x)=24 + 10x3 +5x21115;

17.10.

f(x) = x4 + 2x3 + 2;

 

g(x)=4 3x3 14x2155;

17.11.

f(x) = x4 3x3 8x2 + 12 + 16;

 

g(x)=24 2x3 24x24+16;

17.12.

f(x) = 3x4 + 3x3 20x2 + 17 5;

 

g(x) = 24 16x2 + 24x 10;

17.13.

f(x) = x4 3x3 2x2 + 7 3;

 

g(x) = 4 + 3x3 2 4x + 2;

17.14.

f(x) = 3x4 17x3 2x2 5 15;

 

g(x) = 24 7x329x2+5+20;

17.15.

f(x) = x4 x3 + x2 + 3;

 

g(x) = 4 5x3+6x239;

17.16.

f(x) = x3 4x2 + + 6;

 

g(x) = x3 + 2x2 + 2 + 1;

17.17.

f(x)=5+2x4 + 4x3+10x2+16+12;

 

g(x) = 4 + 2x3 + 3x2 + 2 + 2;

17.18.

f(x) = 3 x2 4x 6;

 

g(x) = 3 + x2 10x 6;

17.19.

f(x) = 4 + x3 3x2   6x 3;

 

g(x) = 3 + 2x2 + 2x + 1;

17.20.

f(x) = 6 + 6x5 4x4+4x3+1228x+4;

 

g(x) = 5 x4 x3 + 222x2;

17.21.

f(x) = 4 + 6x3+ 17x2+24x+12;

 

g(x) = 3 2x2 13x 10;

17.22.

f(x) = 5 + x4 + 3x3 +4x2+4+2;

 

g(x) = 5 + 2x4 + 3x3 + 62 + 6x + 2;

17.23.

f(x) = 6 + 6x5 + 2x3+3x2+6+1;

 

g(x) = 5 + 6x4 + 4x2 + 42 + 4x + 6;

 

17.24.

f(x) = 4 + 2x3 x2   4 2;

 

g(x) = 4 + x3 x2 2 2;

 

17.25.

f(x) = 5 + 3x4 + x3  +2+3x+1;

 

g(x) = 4 + 2x3 + x + 2;

17.26.

f(x) = 44 2x3 16x2  + 5 + 9;

 

g(x) = 23 x2 5x + 4;

 

17.27.

f(x) = 4 + 2x3 + 2x2  + 2 + 2;

 

g(x) = 3 + 3x + 2;

17.28.

f(x) = 4 + x3 + 2x2  + + 1;

 

g(x) = 3 2x2 + x 2;

17.29.

f(x) = 3 4x2 + x + 1;

 

g(x) = 3 + 2x2 + 2x + 1;

17.30.

f(x) = 5 + 2x4 +4x3 +102+16x+12;

 

g(x) = 4 + 2x3 + 3x2 + 2x + 2;

17.31.

f(x) = 6 + x5 3x4  + 23 + 4x 2;

 

g(x) = 5 + 3x4 + x3 + 6x2 + 4x + 6;

17.32.

f(x) = 2x4 x3 3x2 7 12;

 

g(x) = 24 x3 9x2 + 6;

17.33.

f(x) = 5 x3 + 2x2   2 + 2;

 

g(x) = 4 + 2x3 + 7x2 + 2x + 6;

17.34.

f(x) = 3x4 + 14x3 +10x2128;

 

g(x)=44 + 18x3 +12x2128;

17.35.

f(x) = 2x4 4x3 6x2 8 20;

 

g()=44 8x3 19x2 25;

17.36.

f(x) = 4x4 + 16x3 + 5x2 + 4 + 1;

 

g(x) = 34 + 9x3 9x2 3.

 

\..\

                              Copyright © 2008-2009 ..   . .